The Development Of The Song “Jangan Kawin Muda” For Postpone Of Early Marriage In Adolescent (Jurnal Seni Musik, 2022)
Early marriage is one of the problems faced by the Indonesian people, because it has a negative impact on the increase in the divorce rate for young couples. Furthermore, divorce will suffer children, because they do not get the attention and love of their parents, so they become neglected children. One of the causes of early marriage is the lack of information about the bad effects of early marriage. On this basis, this research is a development of previous research (Dariyo, Rahaditya & Hadiati, 2020) with the aim of providing information about the dangers of early marriage, which is realized with the song "Do not marry young". The research method uses the ADDIE approach (Analysis, Design, Development, Implementation & Evaluation). The results of the research that the birth of the song “ Jangan Kawin Muda” was carried out through the ADDIE process. The poems and songs Jangan Kawin Muda have been validated by a music psychologist and 74 teenagers. The song "Jangan Kawin Muda" has fulfilled the rhythm, melody, style, instrument and beat that can be felt positively by teenagers, so that they can understand, memorize and sing the song well. In the end, they are motivated to delay early marriage. On the other hand, the video display still needs improvement with the thematic video clip display of the song.